Synthesis and characterization of functional eugenol derivative based layered double hydroxide and its use as a nanoflame-retardant in epoxy resin1. Issue 7 (21st February 2015) - Li, Cheng; Wan, Jintao; Kalali, Ehsan Naderi; Fan, Hong; Wang, De-Yi
<x xml:space="preserve">Abstract</x> Aiming to develop a multi-functional flame retardant for epoxy resins, a novel bio-based eugenol derivative (SIEPDP) was synthesized, and was used to modify Mg–Al layered double hydroxide (SIEPDP-LDH). This modified SIEPDP-LDH was used as a novel nanoflame-retardant for bisphenol epoxy resins and compared with unmodified pristine LDH.